Exploring active galactic nuclei and little red dots with the Obelisk simulation - Volonteri, Marta; Trebitsch, M.; Greene, J. E.; Dubois, Y.; Dong-Paez, C.-A.; Habouzit, Mélanie; Lupi, A.; Ma, Y.; Beckmann, R. S.; Dayal, P.; Schneider, R. (Astronomy and astrophysics, 2025)
The James Webb Space telescope has discovered an abundant population of broad line emitters, typical signposts for Active Galactic Nuclei (AGN). Many of these sources have red colors and a compact appearance that has led to them being named “little red dots”. In this paper, we develop a detailed framework to estimate the photometry of AGNs embedded in galaxies extracted from the OBELISK cosmological simulation to understand the properties of color-selected little red dots (cLRDs) in the context of the full AGN and massive black hole population. We find that using realistic spectral energy distributions (SEDs) and attenuation for AGNs we can explain the shape of the cLRD SED as long as galaxies host a sufficiently luminous AGN that is neither overly attenuated nor too little attenuated. When attenuation is too low or too high, AGNs do not enter the cLRD selection, because the AGN dominates over the host galaxy too much in blue filters, or it does not contribute to photometry anywhere, respectively. cLRDs are also characterized by high Eddington ratios, possibility super-Eddington ones, and/or high ratios between the black hole and the stellar mass.
Online verfügbar: 28. Februar 2025
Gesehen am 08.09.2025